2007
DOI: 10.1007/s10875-007-9157-0
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-α Induces Up-regulation and Nuclear Translocation of the Ro52 Autoantigen as Detected by a Panel of Novel Ro52-specific Monoclonal Antibodies

Abstract: Interferon-alpha (IFN-alpha) has been implicated in the pathogenesis of Sjögren's syndrome and systemic lupus erythematosus. Ro52, which was recently identified as an E3 ligase with anti-proliferative and pro-apoptotic properties, is a major autoantigen targeted in both these conditions. Microarray analyses have indicated up-regulation of Ro52 by IFN-alpha, and the objective of the present study was to address the potential link between IFN-alpha and Ro52. To investigate the influence of IFN-alpha on Ro52 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 106 publications
(120 citation statements)
references
References 35 publications
4
116
0
Order By: Relevance
“…It has previously been reported that Trim21 expression is induced by both type I and type II IFNs in a variety of cells (20,21,41,42). We confirmed and extended these data by using a mouse T cell line and observed that Trim21 expression is indeed induced by IFNs in a dose-dependent manner and that type I IFNs (especially IFN-b) are more potent at inducing Trim21 transcription than IFN-g (Fig.…”
Section: Ifn-a and Ifn-b Are Potent Inducers Of Trim21 In A Variety Osupporting
confidence: 86%
“…It has previously been reported that Trim21 expression is induced by both type I and type II IFNs in a variety of cells (20,21,41,42). We confirmed and extended these data by using a mouse T cell line and observed that Trim21 expression is indeed induced by IFNs in a dose-dependent manner and that type I IFNs (especially IFN-b) are more potent at inducing Trim21 transcription than IFN-g (Fig.…”
Section: Ifn-a and Ifn-b Are Potent Inducers Of Trim21 In A Variety Osupporting
confidence: 86%
“…The UBED1-4 class I E2s are cytoplasmic, whereas UBE2E1-2 class III E2s are localized to the cell nucleus (32,40). This cellular compartmentalization of E2s may contribute to both temporal and substrate specificity of the ubiquitination process, as Ro52 is predominantly cytoplasmic (1, 7), but translocates into the nucleus upon interferon stimulation (1).…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by the Regional Human Ethics Committee at the Karolinska University Hospital, and informed consent was obtained from all subjects. Monoclonal antibodies against human Ro52 were generated by standard hybridoma protocols and characterized as described previously (1,22).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the autoantibodies are found primarily in the sera of patients with Systemic Lupus Erythematosus (SLE) and Sj€ ogren's Syndrome (SS), they are also found in patients with other systemic autoimmune diseases such as rheumatoid arthritis and systemic sclerosis. [64][65][66][67][68] While the role of TRIM21…”
Section: Spry/b302 Domain-containing Proteins Involved In Innate Celmentioning
confidence: 99%